2020
DOI: 10.1002/mgg3.1189
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐150 serves as a diagnostic biomarker and is involved in the inflammatory pathogenesis of Parkinson's disease

Abstract: Background Dysregulation of microRNAs (miRNAs) has been reported to be involved in the neuroinflammatory pathogenesis of PD. This study aimed to investigate the serum expression of microRNA‐150 (miR‐150) in Parkinson's disease (PD) patients and further uncover the regulatory effect of miR‐150 on neuroinflammation. Methods Quantitative Real‐Time PCR was used to measure the expression of miR‐150. A receiver operating characteristic curve was applied to evaluate the diagnostic value of miR‐150. The effect of miR‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…4B), which suggested that these miRNAs could possibly participate in both iRBD and PD. Consistent with this hypothesis, miR-150-5p expression was previously reported to be dysregulated during PD progression 50 . Extensive research conducted on let-7 revealed that let-7 could be involved in regulating neuronal degeneration in PD 51 and recognized by TLR7 to promote in ammation and neuronal death 52 .…”
Section: Consistently Altered Ev Mirnas In a Healthy-irbd-pd Hierarchysupporting
confidence: 66%
“…4B), which suggested that these miRNAs could possibly participate in both iRBD and PD. Consistent with this hypothesis, miR-150-5p expression was previously reported to be dysregulated during PD progression 50 . Extensive research conducted on let-7 revealed that let-7 could be involved in regulating neuronal degeneration in PD 51 and recognized by TLR7 to promote in ammation and neuronal death 52 .…”
Section: Consistently Altered Ev Mirnas In a Healthy-irbd-pd Hierarchysupporting
confidence: 66%
“…The crucial role of miRNAs in the diagnosis, pathogenesis, and treatment of PD has been reported by many studies [21]. In a previous study, miR-150-5p was observed to be expressed at low level in the serum of PD patients [22]. In addition, high levels of miR-150-5p have also been detected in patients with Alzheimer's disease [23].…”
Section: Discussionmentioning
confidence: 92%
“…MiR-150 expression is decreased in the serum of PD patients and could be as a candidate diagnostic biomarker for PD. Overexpressing miR-150 repressed lipopolysaccharide (LPS) mediated microglial inflammation [ 15 ]. Cai LJ et al found that up-regulating miR-375 alleviated the damage of dopaminergic neurons, and reduced oxidative stress and inflammation by inhibiting SP1 in 6-hydroxydopamine induced PD animal model [ 16 ].…”
Section: Introductionmentioning
confidence: 99%